Do Student Loans in Cambodian Education Matter? A Perspective from Loan Officers - Bunthorn THY; Chantrea Moeurn (Journal of Education Research, 2026)
The microfinance sector in Cambodia has grown rapidly, expanding access to finance for micro-entrepreneurs and low-income households. In the 1990s, it was primarily managed by international non-governmental organizations and significantly contributed to the country’s economic growth, particularly in the education sector. Student loans, furthermore, provided by banks were identified as an important program to help low-income students access higher education. Student loans are especially important for socioeconomically disadvantaged backgrounds, offering opportunities for higher education. However, student loans are rarely discussed in academic literature, specifically their benefits. This study aims to explore the benefits of student loans in Cambodia. To attain the objective, the study utilized a qualitative approach employing a purposive sample. One-on-one interviews were conducted with three experienced officers from the student loan program. The data were analyzed using thematic coding, drawing from both the literature review and emerging patterns.  The results identified four main advantages: (1) Access to higher education; (2) Gain financial responsibility; (3) Invest in human capital, and (4) Reduced family financial pressure. Overall, the study required comprehensive support from the banking sector and higher education institutions in providing more accessible information to students from low-income families. The relevant stakeholders can continue to enhance educational equity for all students, ensuring they have equal opportunities to excel academically and contribute to the human capital development goal, which is essential for supporting Cambodia’s vision by 2030 and 2050.